2022
DOI: 10.3389/fbioe.2022.1072950
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymerized porcine hemoglobin in the ex vivo normothermic machine perfusion of rat livers

Abstract: Background: In contrast to traditional static cold preservation of donor livers, normothermic machine perfusion (NMP) may reduce preservation injury, improve graft viability and potentially allows ex vivo assessment of graft viability before transplantation. The polymerized porcine hemoglobin is a kind of hemoglobin oxygen carrier prepared by crosslinking porcine hemoglobin by glutaraldehyde to form a polymer. The pPolyHb has been proved to have the ability of transporting oxygen which could repair the organ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A porcine hemoglobin-based oxygen carrier (pPolyHb) was shown to have the ability to transport oxygen and repair organ ischemia-reperfusion injury in rats. 91 The latest research found that the natural extracellular hemoglobin (HemO 2 life) isolated from the polychaete Arenicola marina is a potential new hemoglobin oxygen carrier. The molecular weight of HemO 2 life is 50 times that of human hemoglobin, and the binding and release characteristics of oxygen are similar to those of human hemoglobin; it can bind 156 oxygen molecules and also has natural antioxidant properties due to its intrinsic superoxide dismutase activity.…”
Section: Application Of Hbocs 311 Application Of Hbocs In Acute Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…A porcine hemoglobin-based oxygen carrier (pPolyHb) was shown to have the ability to transport oxygen and repair organ ischemia-reperfusion injury in rats. 91 The latest research found that the natural extracellular hemoglobin (HemO 2 life) isolated from the polychaete Arenicola marina is a potential new hemoglobin oxygen carrier. The molecular weight of HemO 2 life is 50 times that of human hemoglobin, and the binding and release characteristics of oxygen are similar to those of human hemoglobin; it can bind 156 oxygen molecules and also has natural antioxidant properties due to its intrinsic superoxide dismutase activity.…”
Section: Application Of Hbocs 311 Application Of Hbocs In Acute Bloodmentioning
confidence: 99%
“…Since tissues and organs will not completely stop metabolism in a low-temperature environment, the lack of metabolic substrates for aerobic respiration will still damage organs. A porcine hemoglobin-based oxygen carrier (pPolyHb) was shown to have the ability to transport oxygen and repair organ ischemia-reperfusion injury in rats . The latest research found that the natural extracellular hemoglobin (HemO 2 life) isolated from the polychaete Arenicola marina is a potential new hemoglobin oxygen carrier.…”
Section: Application Of Oxygen Carriersmentioning
confidence: 99%